Effects of filler types on the microstructural and engineering properties of waste plastic binder composite for construction purposes. Issue 1 (31st December 2022) - Babatunde, Yusuf Olawale; Mwero, John; Mutuku, Raphael; Jimoh, Yinusa; Oguntayo, Daniel
Abstract: Plastic is one of the prominent solid wastes and its ineffective disposal has caused environmental issues. Previous research focused onthe replacement of aggregates with waste plastic in the concrete mix. This study focused on the utilization of waste polyethylene terephthalate (PET) plastic as a binder for construction application. The waste PET plastic was melted and mixed with different filler materials to give a homogenous and uniform mortar/concrete-like composite using different formulation ratio of 1:0, 1:1, 1:2, 1:3. The influence of the filler materials and the varying mix composition on the engineering and morphology properties of the resulting composite was investigated. The morphology of the waste plastic composite samples showed that the filler materials filled the pores present in the molten plastic, thereby reinforcing it. The results indicated that, the density, compressive strength, and water absorption increase as the content of the filler material increases. However, composites of plastic-sand, and plastic-quarry dust at ratio 1:3 gave higher compressive strength values of 20.30 and 20.10 N/mm 2 respectively, which meet up with the minimum requirement of 17 N/mm 2 compressive strength for structural lightweight concrete as specified by ACI and BS standards. Thus, they can be adopted for structural purposes.